1993
DOI: 10.3168/jds.s0022-0302(93)77661-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Management Practices of the Top Milk Producing Herds in the Country

Abstract: Out of 128 surveys mailed to dairy farms that had been identified by the nine DHI processing centers as the top milk producing herds in the country, 61 surveys were returned. The predominant forage being fed was corn silage, followed by legume hay and haylage. On average, 6.7 feed additives and 3.5 alternative feeds were fed. Producers reported the following incidences of metabolic disorders: parturient paresis, 7.2%; displaced abomasum, 3.3%; ketosis, 3.7%; and nonspecific downer cow syndrome, 1.1%. Producers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 21 publications
0
27
0
2
Order By: Relevance
“…A survey of high-producing herds in the United States showed that 91% used corn silage and 58 and 81% were using alfalfa hay and alfalfa silage, respectively (Kellogg et al, 2001). Most producers prefer feeding diets with mixtures of forages rather than a single forage (Jordan and Fourdraine, 1993). Highquality alfalfa silage (AS) and high-quality corn silage (CS) typically contain similar concentrations of NDF as a percentage of DM.…”
Section: Introductionmentioning
confidence: 98%
“…A survey of high-producing herds in the United States showed that 91% used corn silage and 58 and 81% were using alfalfa hay and alfalfa silage, respectively (Kellogg et al, 2001). Most producers prefer feeding diets with mixtures of forages rather than a single forage (Jordan and Fourdraine, 1993). Highquality alfalfa silage (AS) and high-quality corn silage (CS) typically contain similar concentrations of NDF as a percentage of DM.…”
Section: Introductionmentioning
confidence: 98%
“…A survey of the highest producing herds in the United States revealed that over 67% of producers used a TMR feeding system, and that these producers averaged 2.9 groups of cows that were fed 2.7 times daily (Jordan and Fourdraine, 1993). Several researchers have examined various grouping strategies and suggested that cows might best be grouped by nutrient requirements (Sniffen et al, 1993).…”
Section: Factors Influencing Group Size and Number Of Groupsmentioning
confidence: 99%
“…Severe symptoms of hypocalcemia lead to milk fever (Oetzel and Goff 1998). In the United States, milk fever is reported to directly affect 5 to 11% of fresh lactating cows, while subclinical symptoms were evident in up to 50% of the dairy herds [Jordan and Fourdraine 1993;Beede 1996;National Research Council (NRC) 2001]. Economic losses not only include the direct costs of treating animals and decreased milk production, but also secondary problems such as inappetance and predisposition to develop ketosis, retained placenta, displaced abomasum, mastitis, as well as a reduced productive life (Curtis et al 1983;Horst et al 1997;NRC 2001).…”
mentioning
confidence: 99%